Genomic-based genetic parameters and genome-wide association studies for productive and reproductive traits in Beef-on-Dairy crossbreds - Ahmed, R. H.; Schmidtmann, C.; Mugambe, J.; Thaller, G. (Frontiers in Genetics, 2025)
BackgroundBeef on Dairy (BoD) calves are born from the crossing of dairy cows with beef breeds. The genetic architecture of these calves differs significantly from the parent breeds due to heterosis and other dominance effects. Identification of the genomic regions associated with traits in BoD calves and the inheritance pattern of these regions can assist in the selection process. We conducted a genome-wide association study (GWAS) for Belgian blue and Angus crossbreds born from a Holstein dam, incorporating additive and dominance effects to identify genomic regions associated with birth weight, calving difficulty, and gestation length. Additionally, a haplotype-based GWAS was performed to compare the effectiveness of these two different methodologies and to identify the parental origin of the haplotypes based on similar allelic patterns between crossbred and parental breeds.ResultsThe heritability estimates for birth weight, calving difficulty, and gestation length were 0.29 (±0.03), 0.36 (±0.04), and 0.09 (±0.03), respectively. Using SNP-based GWAS for birth weight, a genomic region containing the GABRG1 gene on BTA 6 was identified. In addition, the haplotype-based analysis identified three more genes (CSER1, FAM13A, and LCORL) associated with birth weight. Incorporating dominance effects into the GWAS model led to the identification of an additional gene, SPP1, related to birth weight. For calving difficulty, SNP-based GWAS in Angus crossbreds revealed a genomic region containing the KCNIP4 gene. Most of the haplotypes associated with these traits originated from the three parental breeds, but six unique haplotypes for Angus and Belgian blue were identified.ConclusionBased on this study, Haplotype GWAS was found to have superior statistical power in the identification of associated genomic regions in BoD crossbreds. However, for traits such as calving difficulty, SNP-based GWAS proved to be more effective. Both approaches are essential for the identification of genomic regions associated with traits of interest in BoD calves.